2019
DOI: 10.11591/ijeecs.v14.i1.pp155-168
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of aspects of DDoS attacks detection

Abstract: Distributed Denial of Service attacks (DDoS) are one of the biggest problems facing the Internet. To eliminate this type of attack, the number of which has increased in the period under study, various methods of defense have been proposed. However a detection mechanism that is able to completely counteract the attacks has not yet been found. Therefore, detection and defense against DDoS attacks is of great importance for specialists engaged in computer security. This paper presents a systematic review of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Network behavior-based detection techniques are presented in [18], where the investigation of a large amount of normal traffic and amount of malicious traffic is provided. In [19,20] the systematic review of aspects of DDoS attacks detection and new frameworks are investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Network behavior-based detection techniques are presented in [18], where the investigation of a large amount of normal traffic and amount of malicious traffic is provided. In [19,20] the systematic review of aspects of DDoS attacks detection and new frameworks are investigated.…”
Section: Methodsmentioning
confidence: 99%
“…The study has unique features relevant to the systematic review process. The work in [27] is a systematic review of aspects of distributed denial of service attacks (DDoS). The paper conducted the review using the topics of technique, variable, tools, deployment location and point in time.…”
Section: Related Workmentioning
confidence: 99%
“…Conficker use NBNS (NetBIOS Name Service or netbios-ns) protocol to propagate itself into network [24]. Filtering NBNS protocol in Wireshark will show the information carry out by the NBNS protocol.…”
Section: Netbios Attackmentioning
confidence: 99%
“…Botnets are regularly used to mount DDoS attacks in the Internet. Systematic review on aspects of DDoS detection is conducted and it was found that each technique used for the detection of attacks exploits certain characteristics of the network traffic, user requests and explicit tools [24,25] proposed a technique for the forensics of UDP flood attack that capable to identify the source of UDP flooding bot attack. The UDP flood attack sends an enormous number of UDP packets to any randomly selected ports of a server to block other authentic traffic to the network port.…”
Section: Udp Flood and Dns Amplification Attackmentioning
confidence: 99%